Major Features, Benefits, and Prerequisites for Intelligent Enterprise Managing System - Alexander Ivanovich Olefirenko; Alexey Galuschenko (Research in Social Sciences and Technology, 2018)
The modern conditions of high-tech and highly competitive markets require the evolution of the enterprise automation systems. Such new, the post-ERP systems should meet the conditions for the provision of customer self-service and other counterparts, the dramatic decrease of the manual labour through automation, robotic application, integration with other systems and external contracting systems, multi-channel marketing and distribution, reduction of supply chains and other current trends. These systems should be built on the new IEM Automation Paradigm (Intelligent Enterprise Managing) and therefore belong to the IEM system class. As stated in the IEM paradigm article, a modern approach to solving the task of automation is based on the application of "best" solutions for each separate entity or business unit. In practice, however, this approach has resulted in a series of significant problems. The scale of the problems is increasing with the growth in transactional load, competitive pressures on the market, requirements for accelerate optimization, and business processes changes.